Families in Crisis in the Old South : Divorce, Slavery, and the Law - Schweninger, Loren (Book collections on Project MUSE., 2012)
In the antebellum South, divorce was an explosive issue. As one lawmaker put it, divorce was to be viewed as a form of "madness," and as another asserted, divorce reduced communities to the "lowest ebb of degeneracy." How was it that in this climate, the number of divorces rose steadily during the antebellum era? In Families in Crisis, Loren Schweninger uses previously unexplored records to argue that the difficulties these divorcing families faced reveal much about the reality of life in a slave-holding society as well as the myriad difficulties confronted by white southern families who chose.